Freedom of expression in the Pura Luka Vega drag performance - Perez, Reynald David G. (Animo Repository, 2024)
Last July 10, 2023, Pura Luka Vega portrayed a drag performance that involved elements of the red garb-like costume of the Black Nazarene, while performing a rock-style version of the popular “Our Father” prayer. As a result of their performance, many Filipino Christian groups, some fellow chapters from the LGBTQ+ community, and even those in the national and local positions gave negative criticisms with the performance being branded as “blasphemous” and “offensive.” Several local government units (LGUs) have declared the artist ‘persona non grata’ in those territories. Vega was also arrested one time after charges of violating Article 201 of the Revised Penal Code were filed against them, for “immoral doctrines, obscene publications and exhibitions and indecent shows.” Later on, the artist posted bail worth P72,000. However months later and up until this present day, Pura Luka Vega was arrested and detained for similar charges filed against them. That is why this paper asked if Pura Luka Vega caused harm to the faith of Filipino Catholics, and deserved all the prosecutions. I claimed that the artist had no intention of harming religious sensibilities and, therefore, not deserving of those prosecutions. I argued that the interferences done against PLV are not justified. To back up my argument, I use John Stuart Mill’s Harm Principle in On Liberty, that religious beliefs can be used to instruct people, but not to form an absolute moral dogma. This paper hopes to contribute to the ethical discussions concerning morality, freedom of expression, and religion.